Assessment of factors associated with early and late stage diagnosis of buccal mucosa carcinoma - Padma Ramasamy, Sundaresan Sivapatham (Journal of Applied Pharmaceutical Science, 2016)
Background/Objectives: Delayed reporting at advanced stage of oral cancer is a common problem in India. Hence, the purpose of study was to determine factors associated with early and delay diagnosis of buccal mucosa carcinoma. Materials and Methods: The questionnaire based cross-sectional study was conducted with 198 buccal mucosa carcinoma subjects. Sociodemographic, socioeconomic, clinical-histopathology characteristic, clinical symptoms and their habits were recorded. Results and discussion: In our study, 169(85.3%) had diagnosed with advanced stage, whereas 29(14.7%) diagnosed at early stage. Among all the factors, socioeconomic status, degree of differentiation and regional lymph nodes were found to be associated with stage of diagnosis, whereas sociodemographic, depth of tumor and tumor size were not associated (P
Keywords: Sociodemographic, socioeconomic, early stage, advanced stage, histopathology.